A RETROSPECTIVE COHORT STUDY ASSESSING MORTALITY RISKS IN PATIENTS WITH CRANIOMAXILLOFACIAL TRAUMA AND POLYTRAUMA USING THE INJURY SEVERITY SCORE (ISS) AND THE NEW INJURY SEVERITY SCORE (NISS). - Prabhat, Vinay; Guria, Abhishek; Topno, Rohit; Kundu, Sabyasachi (Student's Journal of Health Research Africa, 2024)
BACKGROUND There is no consistent difference in postoperative complications between early and delayed therapy for craniomaxillofacial trauma and polytrauma patients. Prognosis and fatality risk drive treatment selection. Two assessment scores, Injury Severity Score (ISS) and New Injury Severity Score (NISS) gauge trauma severity objectively, but their accuracy details remain scarce. Data on concurrent craniomaxillofacial trauma patients are limited, with conflicting conclusions among researchers. OBJECTIVE To determine and contrast the threshold (critical) values of the ISS and NISS evaluation scales that indicate the likelihood of a fatal outcome in patients suffering from polytrauma and craniomaxillofacial trauma. MATERIALS AND METHODS A retrospective analysis was conducted. Patients with facial bone fractures, soft tissue traumas, and concurrent injuries were included. Data on demographics, injuries, treatments, and outcomes were collected. ISS and NISS were calculated, and statistical analyses were performed to determine threshold values for predicting fatal outcomes. RESULTS Thirty patients were included, with assaults (43.3%), falls (20%), and motor vehicle accidents (16.7%) being the leading causes of trauma. Craniocerebral traumas (30%) and extremity traumas (23.3%) were common. Fifteen fatal cases (3%) were identified, with cerebral edema (73.3%) being the primary cause of death. Median ISS was 34 (25-41.5) for lethal cases and 4 (2-16) for the overall patient group. Median NISS was 48 (43-57) for lethal cases and 6 (3-22) for the overall patient group. CONCLUSION Both ISS and NISS show comparable efficacy in predicting the likelihood of fatal outcomes. RECOMMENDATIONS In specialized facilities, both signs could be routinely employed to evaluate patient status and prioritize the next steps in therapy.